The impact of remote working on Employee Motivation and Engagement - Subind, Vinayak; Stříteský, Marek; Hořáková, Marie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The purpose of the thesis is to study the positive and negative aspects of remote working and how it affects employees’ motivation and engagement towards their work. The thesis will consist of a theoretical section that reviews the existing literature and research on remote working, motivation, engagement and the common factors affecting them within employees. The methodology section aims to answer the research questions and uses a qualitative method of semi-structured interviews done on employees working at Microsoft HR in Prague. The methodological section allows the reader to understand the experiences of working employees towards remote working and how it affects their motivation and engagement.
Vedoucí práce: Marek Stříteský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses